Are Alcoholism Treatments Effective? The Project MATCH Data: Response - Miller William R (BMC, 2005)
Abstract A response to Cutler RB, Fishbain, DA: Are alcoholism treatments effective? The Project MATCH data BMC Public Health 2005, 5:75.